2015
DOI: 10.4103/0970-9290.176922
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of relationship between oral health behavior, oral hygiene and gingival status of dental students

Abstract: Thus, it is concluded that there is a significant relationship between the oral health behavior, oral hygiene, and gingival status of dental students. Dental students with better self-reported oral health behavior had lower plaque and gingival scores indicating a better attitude toward oral health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 1 publication
1
10
1
3
Order By: Relevance
“…This differs from previous nding [58]. Lalani A et al 's oral health survey of dental students found that oral health behaviours were signi cantly and negatively associated with plaque and gingivitis [59]. The reason for this phenomenon can be explained by the fact that a small percentage (14.8%) of the population in our survey were dental students, and the rest of the college students may not have really learned the correct brushing or oral cleaning methods, which did not play a signi cant role in improving their oral health.…”
Section: Discussioncontrasting
confidence: 90%
“…This differs from previous nding [58]. Lalani A et al 's oral health survey of dental students found that oral health behaviours were signi cantly and negatively associated with plaque and gingivitis [59]. The reason for this phenomenon can be explained by the fact that a small percentage (14.8%) of the population in our survey were dental students, and the rest of the college students may not have really learned the correct brushing or oral cleaning methods, which did not play a signi cant role in improving their oral health.…”
Section: Discussioncontrasting
confidence: 90%
“…31 Whereas, Lalani et al, established a non-significant difference in the plaque and gingival indices between third and final year dental students. 32 The extensive recommendation to prevent periodontal diseases is to floss teeth regularly. 33 Our results discovered that 34% of clinical and 29.6% of preclinical students regularly used dental floss.…”
Section: Discussionmentioning
confidence: 99%
“…A study done on Indian students concluded that teenagers were unable to correctly assess their dental hygiene. The authors attributed this to a lack of oral health self-assessment skills, which resulted in poor oral hygiene [ 7 ].…”
Section: Introductionmentioning
confidence: 99%